Musical Attention Control Training for Psychotic Psychiatric Patients: An Experimental Pilot Study in a Forensic Psychiatric Hospital - van Alphen, R.; Stams, G. J. J. M.; Hakvoort, L. (Frontiers in Neuroscience, 2019)
Poor attention skills constitute a major problem for psychiatric patients with psychotic symptoms, and increase their chances of treatment drop-out. This study investigated possible benefits of Musical Attention Control Training (MACT). To examine the effect of MACT on attention skills of psychiatric patients with psychotic features a Randomized Controlled Trial (RCT) was conducted in a forensic psychiatric hospital. Participants (N = 35, age M = 34.7, 69% male) were pair matched (on age, gender, and educational level), and randomly assigned to an experimental and control group. The experimental group received a 30-minute MACT training once a week over six weeks’ time, whereas the controls received treatment as usual without attention training. Single blind pre- and post-test neuropsychological assessments were performed to measure different attention levels. The experimental MACT group outperformed the control group in selective, sustained and alternating attention. In addition, overall attendance of MACT participants was high (87.1%). This result suggests that in this experimental pilot study MACT was effective for attention skills of psychiatric patients with psychotic features. To obtain larger intervention effects additional research is necessary, with a larger sample and a more specific MACT intervention.